2022
DOI: 10.1186/s12888-022-04255-w
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiota and its metabolites correlate with plasma cytokines in schizophrenia inpatients with aggression

Abstract: Background The pathophysiological mechanisms of aggression are manifold and they may closely interconnect. Current study aimed to determine the gut microbiota and its metabolites, and clarify their correlations with inflammation, oxidation, leaky gut and clinical profiles underlying aggression in schizophrenia (ScZ). Methods Serum and stool specimens from ScZ inpatients with (ScZ-Ag, 25 cases) and without aggression (NScZ-Ag, 25 cases) were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Accumulating evidence suggested the engagement of gut microbiota in neuropsychological diseases [37][38][39]. One previous study reported dramatically reduced alpha and beta diversities in AIS patients with an unfavorable outcome [40], while another study exhibited high similarities for both alpha and beta diversities between ischemic stroke patients and healthy individuals [13].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested the engagement of gut microbiota in neuropsychological diseases [37][38][39]. One previous study reported dramatically reduced alpha and beta diversities in AIS patients with an unfavorable outcome [40], while another study exhibited high similarities for both alpha and beta diversities between ischemic stroke patients and healthy individuals [13].…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs can provide 70% energy fuel for the intestinal epithelial cells to maintain the integrity of intestinal barrier (11). Published studies showed the leaky gut with intestinal barrier dysfunction causing the increase of pathogen-associated molecular patterns (PAMP) in blood to further deteriorate inflammatory response was attributed to the reduction of fecal SCFAs (11,12). Besides, SCFAs can serve to modulate the leukocytes-induced inflammation in different diseases through their special receptor GPR41, 43 and 109A (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal dysbiosis induced by antibiotic treatment is not commonly used. Still, this type of second insult is worth investigating because there is growing evidence that the mammalian digestive tract microbiome affects host physiology, modulates immunity, development, and nutrient uptake [ 75 , 76 ], and that its disruption affects not only physical but also mental health [ 8 ] due to the dysregulation of the gut-microbiome-brain axis [ 3 , 5 , 11 , [77] , [78] , [79] , [80] , [81] ].…”
Section: Introductionmentioning
confidence: 99%